Antagonistic activity of Phomopsis sp. and Fusarium lateritium against three tree pathogens - Augustine, Adeline (2019)
The impact of plant diseases such as brown root rot, wilt, stem and branch cankers, staining of vascular tissues and damping-off has been profound over the centuries. Since the uses of fungicides bring negative impacts to the environment, biological control agent provide the alternative solution to control diseases in an environment-friendly manner. In the present study, the morphology and growth performance of several fungi cultures growing on normal Potato Dextrose Agar (nPDA) and PDA with adjusted pH (7.4) (aPDA) were examined. The growth of Fusarium oxysporum was 3-fold faster than Ceratocystis fimbriata and 2-fold faster than Phellinus noxius on nPDA. The antagonistic activity of endophytic fungi, Phomopsis sp. and Fusarium lateritium against pathogenic fungi, F. oxysporum, P. noxius and C. fimbriata was evaluated through dual culture assay and non-volatile compound test. Based on the results, it was observed that the growth of pathogenic fungi was inhibited strongly by Phomopsis sp. compared to F. lateritium. This shows that between these two endophytic fungi isolates, Phomopsis sp. has potential as a biological control agent against these tested fungal pathogens.